Characteristics of the seasonal cycle of surface layer salinity in the global ocean - F. M. Bingham; G. R. Foltz; M. J. McPhaden (Ocean Science, 2012)
The seasonal variability of surface layer salinity (SLS), evaporation ( E ), precipitation ( P ), E-P , advection and vertical entrainment over the global ocean is examined using in situ salinity data, the National Centers for Environmental Prediction's Climate System Forecast Reanalysis and a number of other ancillary data. Seasonal amplitudes and phases are calculated using harmonic analysis and presented in all areas of the open ocean between 60° S and 60° N. Areas with large amplitude SLS seasonal variations include: the intertropical convergence zone (ITCZ) in the Atlantic, Pacific and Indian Oceans; western marginal seas of the Pacific; and the Arabian Sea. The median amplitude in areas that have statistically significant seasonal cycles of SLS is 0.19. Between about 60° S and 60° N, 37% of the ocean surface has a statistically significant seasonal cycle of SLS and 75% has a seasonal cycle of E-P . Phases of SLS have a bimodal distribution, with most areas in the Northern Hemisphere peaking in SLS in March/April and in the Southern Hemisphere in September/October. The seasonal cycle is also estimated for surface freshwater forcing using a mixed-layer depth climatology. With the exception of areas near the western boundaries of the North Atlantic and North Pacific, seasonal variability is dominated by precipitation. Surface freshwater forcing also has a bimodal distribution, with peaks in January and July, 1–2 months before the peaks of SLS. Seasonal amplitudes and phases calculated for horizontal advection show it to be important in the tropical oceans. Vertical entrainment, estimated from mixed-layer heaving, is largest in mid and high latitudes, with a seasonal cycle that peaks in late winter. The amplitudes and phases of SLS and surface fluxes compare well in a qualitative sense, suggesting that much of the variability in SLS is due to E-P . However, the amplitudes of SLS are somewhat different than would be expected and the peak of SLS comes typically about one month earlier than expected. The ...